Does Buprenorphine Decrease the Risk of Neonatal Abstinence Syndrome in Mothers with Opioid use Disorder? [26N]. (May 2018) - Ly, Victoria; Persad, Malini D.; Herrera, Kimberly; Garry, David; Garretto, Diana
Abstract : INTRODUCTION: The objective of this study is to determine if buprenorphine opioid maintenance therapy is associated with a decrease risk of neonatal abstinence syndrome in mothers with opioid use disorder. METHODS: A retrospective cohort study of pregnant women with opioid use disorder was performed at a tertiary care hospital from January 2016 to June 2016. Women were identified using the hospital's delivery logs. Women were categorized by opioid maintenance therapy type: buprenorphine or methadone. Maternal demographics, medical history, social history, maintenance therapy type, delivery characteristics and neonatal outcomes were collected from the electronic medical record. A composite adverse neonatal outcome score was created and defined as the presence of any of the following characteristics: preterm delivery, low birth weight <2500 g, Apgar score < 7 at 5 minutes, NICU admission, and neonatal abstinence syndrome. Parametric and nonparametric statistics were used to compared groups as appropriate. A p value of < .05 was considered statistically significant. RESULTS: Of 1, 927 women who delivered, 37 women qualified for the study. There was no statistically significant difference in demographic characteristics between groups. Additionally, there were no statistically significant differences in neonatal outcomes, including neonatal abstinence syndrome, between women who received buprenorphine maintenance therapy compared to those who received methadone maintenance therapy. CONCLUSION: Buprenorphine has a comparable incidence of neonatal abstinence syndrome to methadone in the treatment of opioid use disorder in pregnancy. Providers can consider the use of either agent with treating women with this condition.